The association between polymorphisms near TMEM18 and the risk of obesity: a meta-analysis - Natalia Koj; Łukasz Grochowalski; Justyna Jarczak; Weronika Wójtowicz; Marta Sobalska-Kwapis; Marcin Słomka; Błażej Marciniak; Dominik Strapagiel (BMC, 2021)
Abstract Background Many studies have proposed that the pathogenesis of obesity has a genetic basis, with an important risk factor being the presence of polymorphisms in the region of the TMEM18 gene, which plays a significant role in feeding behaviour; however, subsequent studies among different ethnic populations and age groups have shown inconsistent results. Therefore, this present meta-analysis examines the relationship between TMEM18 polymorphisms with the risk of obesity with regard to age group and ethnic population. Methods A literature database search was conducted for available relevant studies investigating the association between obesity risk and the presence of rs6548238, rs4854344, rs11127485, rs2867125 and rs7561317 polymorphisms in TMEM18. Pooled odds ratio (OR) and 95% confidence intervals (95% CI) were calculated by either a fixed-effects model or random effect model based on a heterogeneity test. The meta-analysis of rs6548238 and its surrogates examined the relationships between 53 395 obesity cases and 123 972 healthy controls from 27 studies and published data from the POPULOUS collection (Poland). Results A significant association is observed between rs6548238 (and surrogate) and obesity risk, with OR = 1.25 (95% CI: 1.08-1.45). Regarding population type, a significant association was revealed among groups of Europeans with OR = 1.32 (1.10-1.59) and Mexicans with OR = 1.39 (1.13-1.73). However, a lack of statistical significance was noticed in groups in Asia with OR = 1.11 (95% CI: 0.86-1.42). Regarding age, a significant association was observed among children with OR = 1.28 (95% CI: 1.18-1.39) but not in adults OR = 1.21 (95% CI: 0.92-1.58). Conclusions The polymorphisms near TMEM18 appear to play a role in the development of obesity. Our findings indicate that differences exist between ethnic populations and age groups, supporting those of a previous study showing the various effects of genetic factors on age and ethnic groups.